The SAMI Galaxy Survey: shocks and outflows in a normal star-forming galaxy. Issue 4 (18th September 2014) - Ho, I-Ting; Kewley, Lisa J.; Dopita, Michael A.; Medling, Anne M.; Allen, J. T.; Bland-Hawthorn, Joss; Bloom, Jessica V.; Bryant, Julia J.; Croom, Scott M.; Fogarty, L. M. R.; Goodwin, Michael; Green, Andy W.; et al.
Abstract : We demonstrate the feasibility and potential of using large integral field spectroscopic surveys to investigate the prevalence of galactic-scale outflows in the local Universe. Using integral field data from the Sydney-AAO Multi-object Integral field spectrograph (SAMI) and the Wide Field Spectrograph, we study the nature of an isolated disc galaxy, SDSS J090005.05+000446.7 ( z = 0.053 86). In the integral field data sets, the galaxy presents skewed line profiles changing with position in the galaxy. The skewed line profiles are caused by different kinematic components overlapping in the line-of-sight direction. We perform spectral decomposition to separate the line profiles in each spatial pixel as combinations of (1) a narrow kinematic component consistent with H ii regions, (2) a broad kinematic component consistent with shock excitation, and (3) an intermediate component consistent with shock excitation and photoionization mixing. The three kinematic components have distinctly different velocity fields, velocity dispersions, line ratios, and electron densities. We model the line ratios, velocity dispersions, and electron densities with our mappings iv shock and photoionization models, and we reach remarkable agreement between the data and the models. The models demonstrate that the different emission line properties are caused by major galactic outflows that introduce shock excitation in addition to photoionization by star-forming activities. Interstellar shocks embedded in the outflows shock-excite and compress the gas, causing the elevated line ratios, velocity dispersions, and electron densities observed in the broad kinematic component. We argue from energy considerations that, with the lack of a powerful active galactic nucleus, the outflows are likely to be driven by starburst activities. Our results set a benchmark of the type of analysis that can be achieved by the SAMI Galaxy Survey on large numbers of galaxies.